Cooperativa de Catadores de Materiais Recicláveis: um estudo sobre a precarização e a organização do trabalho em Foz do Iguaçu/PR (1990-2009) - Pelisser, Sônia (2010)
This research discusses forms of labor organization among collectors of recyclable materials, in the city of Foz do Iguaçu, both those organized in cooperatives or in informal and family groups, and those who work independently, without any bonds. In order to understand the ways by which cooperatives emerge, in the XIXth century, gathering and review of literature on the subject was made, allowing for evidence that initiative of such a manner of selforganization of workers rose out of opposition to capitalist society. Nonetheless, the cooperative analyzed in the investigation does not function under the expressed assumptions about this kind of organization, mainly because cooperatives within that historical context started from workers free gumption, and in the case under analysis the State (specifically the Municipality of Foz do Iguaçu and the Itaipu Binational entrepreneurship) foments the creation of sorting centers in the city (warehouses belonging to the collectors cooperative participating in the Solidary Collection Program ). From this point, relationships among these workers, their ways of organization, and the State s initiatives were investigated through the analysis of pertinent legislation, journalistic sources and public documents produced regarding those collectors. Such an effort tried to evidence, and understand social pressures collectors have to face in order to constitute themselves as workers, and to reaffirm both their labor and their presence in the city. Finally, labor relations and collectors organization in Foz do Iguaçu are discussed, grounded on the interviews realized with the subjects, with emphasis upon how these latter perceive, and explain their own trajectory as workers up to the present time. Such was the way to get access to tensions and confrontations collectors have to experience, and to discuss them, in special regarding their relationship with the State. In opposition to the concepts of citizenship and social inclusion that many times appear as justifications in the official documents studied, this work focus on the notions developed and interpreted by the collectors themselves